Draft Annual Plan 1990-91 Part-II Statements Union Territory of Delhi - Planning Commission (Planning Commission, 1990)
Major Heads of Development/outlay and Expenditure Statement Agency wise proposed outlay 1990-91 Statement GN-2 Scheme-wise outlay and Expenditure and GN-3-Physical Targets and Achievements.
Planning Department, Delhi Administration